Mapping non-native invasive species and accessibility in an urban forest: A case study of participatory mapping and citizen science in Atlanta, Georgia. (January 2015) - Hawthorne, T.L.; Elmore, V.; Strong, A.; Bennett-Martin, P.; Finnie, J.; Parkman, J.; Harris, T.; Singh, J.; Edwards, L.; Reed, J.
Abstract: We present a participatory methodology for mapping and analyzing urban forests and greenspaces with a particular emphasis on identifying the location and intensity of non-native invasive plant species in a 180-acre nature preserve in Atlanta, Georgia, USA. The research uses smart phone and tablet data collection techniques with GPS to understand the extent and intensity of non-native invasive species distributions. Inverse Distance Weighted spatial interpolation techniques are used in GIS to analyze the data. Results are field validated and presented in a series of GIS maps. Chinese Privet covered 454, 639 m 2 of the mapped area. The species was found in close proximity to many small streams and a major creek. English Ivy occupied the second largest amount of total ground cover, canvassing more than 244, 452 m 2 . The species was generally found near residential edges of the nature preserve. As a contribution to the Public Participation GIS literature, the methodology presented in this article has practical and methodological implications for GIS and urban researchers and practitioners interested in utilizing participatory methodologies for urban forest and greenspace management, restoration efforts, and non-native invasive species monitoring. Highlights: Chinese Privet covered 454, 639 m 2 of the mapped area. English Ivy occupied more than 244, 452 m 2 of the mapped area. Methodology has implications for participatory methodologies in urban greenspaces.